The investigation of dangerous geological processes resulting in land subsidence while designing the main gas pipeline in South Yakutia; IOP Conference Series: Earth and Environmental Science; Vol. 43 : Problems of Geology and Subsurface Development - Strokova L. A. Ludmila Aleksandrovna (Geoecology and Environmental Protection, 2016)
Title screen